Examining Feminist Pedagogy from the Perspective of Transformative Learning: Do Race and Gender Matter in Feminist Classrooms? - Misawa, Mitsunori; Johnson-Bailey, Juanita (International Journal for Talent Development and Creativity, 2024)
Although feminist pedagogy has been widely used as a teaching approach in classrooms in higher education to enhance diversity, issues of race and gender are often areas of contestations for non-White faculty. The purpose of this study was to explore how non-White professors, a Black woman tenured full professor and a gay Asian male pre-tenured professor, co-created a feminist classroom and how they negotiated power in that classroom environment. The research questions that guided this study were: 1) what does a feminist classroom look like in higher education; 2) how does the intersection of race and gender influence feminist pedagogy; and 3) what strategies do adult educators and practitioners use to deal with disoriented dilemmas? This research progressed into a longitudinal study, focusing on how the faculty members’ praxes grew from critical classroom incidents that the professors believed directly related the negative reactions from students to their positionalities as a Black woman and an Asian man. Three themes emerged from the data: a) Confrontation, b) Resistance, and c) Hostility. Each of these themes are defined and presented through direct quotes from our teaching logs and students’ reflections. Discussion and implications for practice are also provided regarding how race and gender matter in feminist classrooms. The concluding section describes how the two faculty members implemented reflective practices in higher education to create feminist classrooms.